2012
DOI: 10.1038/ncomms1659
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of flight promotes beetle diversification

Abstract: The evolution of flight is a key innovation that may enable the extreme diversification of insects. Nonetheless, many species-rich, winged insect groups contain flightless lineages. The loss of flight may promote allopatric differentiation due to limited dispersal power and may result in a high speciation rate in the flightless lineage. Here we show that loss of flight accelerates allopatric speciation using carrion beetles (Coleoptera: Silphidae). We demonstrate that flightless species retain higher genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
135
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 46 publications
9
135
0
2
Order By: Relevance
“…The New Guinean fauna is very poorly known, however based on current knowledge sympatry levels are very low with a maximum of two species known from any locality. As male genitalic morphology in carabid beetles has been shown to be controlled by relatively few genes (Sasabe et al 2007), large amounts of infraspecific genitalic variation in depauperate Mecyclothorax faunas support the presence of abundant genetic variability in and among populations of these flightless species (Liebherr 1988, Ikeda et al 2012. Thus the patterns of variation observed among these anatomically variable species supports the existence of genetic variation sufficient for subsequent diversification and adaptation as observed in the hyperdiverse island radiations.…”
Section: Mecyclothorax Genitalic Evolutionmentioning
confidence: 69%
“…The New Guinean fauna is very poorly known, however based on current knowledge sympatry levels are very low with a maximum of two species known from any locality. As male genitalic morphology in carabid beetles has been shown to be controlled by relatively few genes (Sasabe et al 2007), large amounts of infraspecific genitalic variation in depauperate Mecyclothorax faunas support the presence of abundant genetic variability in and among populations of these flightless species (Liebherr 1988, Ikeda et al 2012. Thus the patterns of variation observed among these anatomically variable species supports the existence of genetic variation sufficient for subsequent diversification and adaptation as observed in the hyperdiverse island radiations.…”
Section: Mecyclothorax Genitalic Evolutionmentioning
confidence: 69%
“…In implementing further studies, the correlation of life-history traits and rates of diversification would be of interest, since it is reported that the ability of migration of avian species might slow down the rate of speciation of taxa (Ikeda et al, 2012;Claramunt et al, 2012). Analyses of the correlation between functional traits and rates of diversification would offer some insights into The best-fitted model is marked in boldface.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advantages associated with flight, such as the ability to disperse widely and forage, flight has been independently lost within nearly every pterygote order and an estimated thousands of times overall [4,5]. The lower dispersal ability associated with flight loss tends to increase population subdivision [6,7], with population subdivision expected to reduce the effective population size (N e ) of species [8]. Lower dispersal ability may additionally reduce geographical range size (reviewed in [9]) and cause greater fluctuations in population size over time owing to increased susceptibility of (sub)populations to extinction, both of which could limit the N e of a species [10].…”
Section: Introductionmentioning
confidence: 99%